A Unified Analysis of the Fault Tolerance Capability in Six-Phase Induction Motor Drives - Munim, W.N.W.A.; Duran, M.J.; Che, Hang Seng; Bermudez, M.; Gonzalez-Prieto, I.; Rahim, Nasrudin Abd (Institute of Electrical and Electronics Engineers, 2017)
The fault tolerance of electric drives is highly appreciated at industry for security and economic reasons, and the inherent redundancy of six-phase machines provides the desired fault-tolerant capability with no extra hardware. For this reason some recent research efforts have been focused on the fault-tolerant design, modeling, and control of six-phase machines. Nevertheless, a unified and conclusive analysis of the postfault capability of six-phase machine is still missing. This paper provides a full picture of the postfault derating in generic six-phase machines and a specific analysis of the fault-tolerant capability of the three mainstream six-phase induction machines (asymmetrical, symmetrical, and dual three phase). Experimental results confirm the theoretical post fault current limits and allow concluding, which is the best six-phase machine for each fault scenario and neutral arrangement.